The Role of Self-Directed Learning in Enhancing Scientific Reasoning Skills: Integrating Project-Based Learning for Biology Education Students - Jaharudin, Jaharudin; Mochamad Cholily, Yus; Pantiwati, Yuni; Andi Hidayat, Febrian; Rachman Tiro, Abdul; Citraningrum, Mivtha; Syamsulrizal; Santoso, Budi; Sirojjuddin; Alia Ulfa, Nurul; Hidayatussakinah (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
This study examines the effectiveness of integrating Self-Directed Learning (SDL) and Project-Based Learning (PjBL) in enhancing students' scientific reasoning skills in biology education. An explanatory sequential mixed-methods design was employed, combining a quasi-experimental one-group pretest–posttest design with qualitative exploration. The participants were 30 undergraduate students in biology education. Quantitative data were collected using a scientific reasoning test, while qualitative data were obtained through semi-structured interviews and reflective writings. The results showed a significant improvement in students’ scientific reasoning scores (p < 0.001) with a very large effect size (Cohen’s d = 2.35). Qualitative findings indicated that learning independence, authentic problem-solving, metacognitive reflection, and scientific collaboration contributed to this improvement. The integration of SDL and PjBL fosters a student-centered learning environment that supports cognitive and metacognitive development. This study offers an integrated pedagogical model and practical implications for enhancing higher-order thinking skills in biology education. Peran Self-Directed Learning dalam Meningkatkan Kemampuan Penalaran Ilmiah: Integrasi Project-Based Learning pada Mahasiswa Pendidikan Biologi ABSTRAK: Penelitian ini bertujuan mengkaji efektivitas integrasi Self-Directed Learning (SDL) dan Project-Based Learning (PjBL) dalam meningkatkan kemampuan penalaran ilmiah mahasiswa pendidikan biologi. Penelitian menggunakan desain explanatory sequential mixed methods dengan pendekatan kuasi-eksperimen one-group pretest–posttest dan eksplorasi kualitatif. Sebanyak 30 mahasiswa berpartisipasi dalam penelitian ini. Data kuantitatif diperoleh melalui tes penalaran ilmiah, sedangkan data kualitatif dikumpulkan melalui wawancara semi-terstruktur dan refleksi tertulis. Hasil menunjukkan adanya peningkatan signifikan pada skor penalaran ilmiah mahasiswa (p < 0,001) dengan ukuran efek sangat besar (Cohen’s d = 2,35). Temuan kualitatif mengungkap bahwa kemandirian belajar, pemecahan masalah autentik, refleksi metakognitif, dan kolaborasi ilmiah berkontribusi terhadap peningkatan penalaran ilmiah. Integrasi SDL dan PjBL menciptakan lingkungan pembelajaran yang berpusat pada mahasiswa serta mendukung proses kognitif dan metakognitif. Penelitian ini berkontribusi dalam pengembangan model pembelajaran terintegrasi untuk meningkatkan keterampilan berpikir tingkat tinggi dalam pendidikan biologi